The University at the Crossroads of Eco-Social Challenges: Pedagogy of Care and the Community of Life for a Transformative Learning - López-López, María Carmen; Martínez-Rodríguez, Francisco Miguel; Fernández-Herrería, Alfonso (Frontiers in Sustainability, 2021)
What kind of responsibility do universities have with regard to the current emergency created by ecological and socio-economic collapse? This work begins by considering the colonisation of universities by neoliberal globalisation. Education is one of the areas that appears as a fundamental source of business in the globalised economy, thus reorienting the role of the State in accordance with the NPM’s (New Public Management) educational policy. The NPM is the main instrument responsible for modifying the structure and culture of state services by means of introducing privatisation and market-specific mechanisms. But, in so doing, something very important is created: a process of ‘re-culturing’, the establishment of the ‘one-track thinking’. It is ‘endogenous neoliberalism’ that promotes the construction of a new identity: the neoliberal view of education from the ‘entrepreneurial self’. Next, and based on the criticism of the Frankfurt School, we question whether the use of reason –as instrumental reason– exists in neoliberal logic, and how it use is related to morals and ethics. We need alternative ideas that configure a new worldview for a new scenario, one which facilitates a deep civilizational reconstruction. The Community of Life is the fundamental certainty on which we can base a new worldview. We are one human family and, even more, one Earth Community with a common destiny. This perspective exists at an even more inclusive level, in order to integrate all living beings. We need care for the community of life with understanding, compassion and love. It implies a synthesis, which places us at the doors of wisdom. The ethics of care and its educational translation as Pedagogy of Care, should have, as its main objective, the experiential learning of our reconnection with the Community of Life. Therefore, it would be necessary a truly transformative learning that we, as humanity, will need to carry out. This is where universities are called on to play a strategic role. The changes that must take place in universities have to be based on a new worldview: the Ethics of Care of the Community of Life. Finally, some practical consequences are proposed in this sense.